Functional movement screen and Y-Balance test scores across levels of American football players - Lisman, P.; Nadelen, M.; Hildebrand, E.; Leppert, K.; de la Motte, S. (Biology of Sport, 2018)
Few studies have investigated differences in functional movement assessment performance across scholastic levels of competition. This study examined Functional Movement Screen (FMS) performance in middle school (MS), high school (HS) and collegiate (COL) American football players and Y-Balance test (YBT) scores in MS and HS players. Functional movement measurements were collected for MS (N = 29; age = 12.8 ± 0.7 years), HS (N =52; age = 15.7 ± 1.2 years), and COL (N =77; age = 19.9 ± 1.4 years) football players prior to each group`s competitive season. Differences in composite FMS and YBT measurements were examined using Welch`s ANOVA and Mann-Whitney U-tests, respectively. Chi-square analyses examined normality of score distributions for individual FMS tests. The MS group displayed a lower composite FMS (12.9 ± 1.9) than both HS (14.0 ± 1.7) and COL (14.1 ± 2.1) groups (p = 0.019). COL players scored significantly lower on the Shoulder Mobility (SM) but higher on the Deep Squat (DS), In-line Lunge (ILL), Active Straight-Leg Raise (ASLR) and Push-Up (PU) than both HS and MS groups. No differences were found between MS and HS groups for any YBT normalized reach distances and side-to-side reach distance differences. FMS performance varied with football competition level whereas YBT performance did not. The results suggest that football competition levels normative data and injury-risk thresholds should be established when using FMS scores to guide performance and injury prevention programming.